Factores clinicopatológicos asociados a la amplificación del gen HER2/neu en pacientes con cáncer de mama HER2 2+ - Meléndez Guevara, Rosa América (2018)
Introduction: A subgroup of breast carcinomas overexpress epidermal growth factor-2 (HER2). The determination of this overexpression is carried out by immunohistochemistry. The difficulty of diagnosis by this method arises when the result is ambiguous (2+), thus it is necessary to perform in situ hybridization (ISH) to determine the amplification of the HER2/neu gene. Objective: To determine if, in HER2 2+ cases, the amplification of the HER 2 / neu gene is associated with prognostic clinicopathological factors. Design: Observational, cross-sectional, descriptive study. Institution: Surgical pathology service, Guillermo Almenara Irigoyen Hospital. Lima, Peru. Participants: Cases of breast cancer HER2 2+. Methodology: We studied 117 cases of Her2 2+ breast cancer diagnosed between the years 2010 - 2015, to which ISH was subsequently performed. All the data were analyzed with the statistical program SPSS 22. The Chi-square test was used to analyze the association between the variables. Main results measures: Factors associated with the amplification of the HER2 / neu gene. Results: Amplification of the HER2 / neu gene was observed in 41% of the total cases. In these, a histological grade III (66%), lymph node involvement (61%), tumor size ≥ 2 cm (86%) and Ki 67 ≥ 20% (83%) were observed more frequently. A statistically significant association was found with an age ≥ 50 years (X2 test, P = 0,004) and histological grade III (X2 test, P = 0.017). Conclusion: Amplification of the HER2/ neu gene in ambiguous cases is associated with an age ≥50 years and histological grade III